Toward a Holistic Framework for Human-Information Interaction - Parsons, Paul; Sedig, Kamran (Proceedings of the Annual Conference of CAIS / Actes du congrès annuel de l’ACSI, 2013)
This poster presents four frameworks that characterize different facets of human-information interaction and examines how they may be integrated in a holistic manner. The resulting framework can inform the analysis, evaluation, and design of all types of interactive tools that support and enable a wide range of information-based cognitive activities. Cette affiche présente quatre cadres caractérisant différentes facettes de l’interaction humain–information et examine comment elles peuvent être intégrées de manière holistique. Le cadre résultant permet d’information l’analyse, l’évaluation et la conception de tout type d’outils interactif appuyant et ouvrant la voie à une vaste gamme d’activités informationnelles cognitives.